Post-Acquisition Restructuring as Evolutionary Process - Meyer, Klaus E.; Lieb-Dóczy, Enese (Journal of management studies, 2003)
ABSTRACT The transformation and integration of acquired businesses is subject to tensions between implementing radical change to match the strategy and corporate culture of the acquirer, and promoting what is valuable in resources and cultural attributes in the acquired organization. Analysts’ disagreement arises from different conceptualizations of the nature of resources. We present an evolutionary perspective that demonstrates not only the merits of competitive selection, but of local adaptation of transferred resources and of stimulating the development of local ones. Evidence from 18 original case studies in Hungary and East Germany shows that a defensive focus on short‐term efficiency, i.e. downsizing, may fail to realize the long‐term potential of the organization. Acquirers supporting an evolutionary development of their new subsidiary by providing autonomy and complementary resources might well have to tolerate some slack in the short run, but may realize more of the potential contributions of the acquired assets in the long run.